Molecular characteristics and evaluation of the phenotypic detection of carbapenemases among Enterobacterales and Pseudomonas via whole genome sequencing - Liang, Bingshao; Chen, Yuou; Liang, Zhuwei; Li, Xueying; Cai, Hao; Lai, Hanyu; Zhong, Huamin; Xie, Yongqiang; Huang, Lianfen; Gao, Fei; Long, Yan (Frontiers in Cellular and Infection Microbiology, 2024)
Background/Purpose(s): The continuously increasing carbapenem resistance within Enterobacterales and Pseudomonas poses a threat to public health, nevertheless, the molecular characteristics of which in southern China still remain limited. And carbapenemase identification is a key factor in effective early therapy of carbapenem-resistant bacteria infections. We aimed to determine the molecular characteristics of these pathogens and compare commercial combined disc tests (CDTs) with the modified carbapenem inactivation method (mCIM) and EDTA-CIM (eCIM) in detecting and distinguishing carbapenemases using whole genome sequencing (WGS).Methods: A total of 78 Enterobacterales, 30 Pseudomonas were obtained from two tertiary hospitals in southern China. Susceptibility tests were conducted using an automated VITEK2 compact system with confirmation via the Kirby-Bauer method. The WGS was conducted on all clinical isolates and the molecular characteristics were analyzed by screening the whole genome sequences. CDTs with or without cloxacillin, mCIM, and eCIM, were performed and compared by taking WGS results as the benchmark.detected and differentiated carbapenemases among Enterobacterales isolates, and the former performed better than CDT among Pseudomonas.